Does the Association between Guardians’ Sense of Coherence and their Children’s Untreated Caries Differ According to Socioeconomic Status? - Mizuta, Akiko; Aida, Jun; Nakamura, Mieko; Ojima, Toshiyuki (International journal of environmental research and public health, 2020)
Untreated caries is the most prevalent disease in the world. A sense of coherence (SOC) is believed to contribute to oral health. We aimed to clarify the association between guardians’ SOC and their children’s caries based on socioeconomic status (SES) in Japan. This study’s subjects were Japanese public junior high schoolers (N = 1730), aged 12–15, and their guardians in Kosai City. We administered a questionnaire survey among guardians in 2016 to assess their SOC and family environment. With their students’ consent, public junior high schools shared the results of the dental examinations that were part of their school physicals. Multivariate logistic regression was conducted to clarify the association between guardians’ SOC and their children’s untreated decayed permanent teeth. We also conducted a stratified analysis according to a relative poverty line. We observed in the multivariate regression a significant inverse association between children’s untreated decay and their guardians’ SOC (OR 0.93, 95%CI 0.87–1.00). The association of SOC was stronger in the low economic group (OR 0.64, 95%CI 0.43–0.95). Guardians with higher SOC were associated with children having fewer caries. Guardians’ SOC is a factor for the prevalence of caries and access to dental care, especially among children with low economic status.